The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1017/s104161022100106x
|View full text |Cite
|
Sign up to set email alerts
|

Delirium occurrence and association with outcomes in hospitalized COVID-19 patients

Abstract: Delirium is reported to be one of the manifestations of coronavirus infectious disease 2019 (COVID-19) infection. COVID-19 hospitalized patients are at a higher risk of delirium. Pathophysiology behind the association of delirium and COVID-19 is uncertain. We analyzed the association of delirium occurrence with outcomes in hospitalized COVID-19 patients, across all age groups, at Mayo Clinic hospitals. A retrospective study of all hospitalized COVID-19 patients at Mayo Clinic between March 1, 2020 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 9 publications
(22 reference statements)
2
15
0
Order By: Relevance
“…With a mean age of 81.7±4 years and a huge prevalence of the male sex, the cases described in the present study appear to follow the evidence in the literature, which report a greater risk of developing delirium in males and among the elderly, a well as among patients hospitalized for COVID-19 (75)(76)(77)(78)(79).…”
Section: Discussionsupporting
confidence: 86%
“…With a mean age of 81.7±4 years and a huge prevalence of the male sex, the cases described in the present study appear to follow the evidence in the literature, which report a greater risk of developing delirium in males and among the elderly, a well as among patients hospitalized for COVID-19 (75)(76)(77)(78)(79).…”
Section: Discussionsupporting
confidence: 86%
“…The unstructured clinical notes and semi-structured flowsheet data can improve phenotyping sensitivity by approximately 20% over a purely structured data (ICD-based) approach. [8][9][10] Similar results were achieved with incidental findings, 11 diseases with multifactorial causes, 9,12 diseases with no singular and conclusive diagnostic tests, 13 or surgical information. 13,14 Furthermore, to maximize the detection accuracy, studies have leveraged the combination of both structured (e.g., laboratory and medication) and unstructured data to determine patient's disease status, such as silent brain infarction, 15 type 2 diabetes mellitus, 16 and rheumatoid arthritis.…”
Section: Introductionsupporting
confidence: 70%
“…Studies of delirium to date in patients with COVID‐19 have suggested prevalence rates from 12% to 84% [30–32]. This disparity reflects the challenges in recognition and the diversity of settings.…”
Section: Prevalence and Incidencementioning
confidence: 99%
“…Studies of delirium to date in patients with COVID-19 have suggested prevalence rates from 12% to 84% [30][31][32].…”
Section: Prevalence and Incidencementioning
confidence: 99%